Analisis Kapasitas Fiskal Daerah: Studi Kasus di Kabupaten Gunung Kidul - Jaka Sriyana (Universitas Islam Indonesia, 2009)
Intergovernmental fiscal transfers are critical elements of public finance indecentralized countries. In the context of Indonesia’s decentralization reforms,their design and implementation have significant impacts on the potential revenueand fiscal capacity of basic public service provision. The case of Indonesia’s 2001Big Bang decentralization illustrates the challenges associated with implementingsignificant reforms in the intergovernmental fiscal system. The practice ofdecentralization policy in Indonesia since the time has not generally improvedlocal development performance yet. This study evaluates fiscal decentralization,focusing on fiscal capacity as the impacts of the intergovernmental fiscalequalization transfers, in the case of Gunung Kidul, Yogyakarta. The study showsa low percentage of its own revenue compared to its total budget. It indicates thefailure of fiscal decentralization policy in improving local government fiscalcapacity.